The effect of injection of ADSC compared to APPE on collagen density in aging skin (animal study) - Pricilla, Erlina; Julianto, Indah; Kariosentono, Harijono; Budiani, Dyah R; Fibrianto, Yuda Heru; Rindiastuti, Yuyun; Veraida, Ainun (Journal of General - Procedural Dermatology and Venereology Indonesia, 2017)
Introduction: Aging is a biological process that can induces changes to the structural integrity and physiological function of skin. Structural changes of skin are a result of dermal atrophy, decreased collagen, the loss of subcutaneous fat, the loss of inherent elasticity, and increased melanogen.1,5,6 From the definition itself, a stem cell characterized by its ability to self-renew and also have an ability to differentiate along multiple lineage pathways.2,4 ADSC which is a kind of mesenchymal stem cell from human adipose tissue, have some potential properties as stem cells derived from bone marrow.4,7 Objective: The aim of this study was to verify the comparison effect of ADSCs and their secretome for skin aging treatment. Methods: ADSC were isolated from lipoaspirates obtained from healthy donors after obtaining written consent and ethical approval using liberase enzymatic digestion, washed with steril PBS and centrifuged. After the phase, ADSC were seeded directly after isolation with liberases and cultured, then produced the conditioning media (AAPE) by hypoxia amplifies.3,4,6,7 We analysed the ADSCs (2,5 x 105 cells) and their secretomes (0,1ml in 0,4ml NaCl 0,9%) by subcutaneous injection on the back of a rat (with range age 48 weeks), and followed began every two weeks after injected until six weeks and stained with Van Giesson staining, for measured the density of collagen.3,5,6 Results: Collagen density was increased after ADSC injected to the skin. From statistical analysis showed there was a significant result of collagen density compared to control group and AAPE (p<0.05). We conclude that ADSC had anti-aging potential or regenerative by stimulating collagen synthesis of dermal fibroblast. ADSC will be as new modality treatment for aging skin in future.